Analysis of the Effectiveness of Educational Management Strategies through Current Practices in Improving the Quality of English Language Learning in Educational Institutions - Yasysyar Hidayat (Yayasan Putra Adi Dharma, 2024)
Effective educational management strategies play a crucial role in enhancing the quality of English language learning in educational institutions. This study explores the impact of curriculum design, teacher training, and technology integration on language learning outcomes. Through a mixed-methods approach, data was collected from teachers, students, and administrators in secondary schools and universities. Findings indicate that well-designed curricula, ongoing teacher training, and the effective integration of technology significantly improve student engagement and language proficiency. However, challenges such as resource limitations and resistance to change persist. Recommendations include increased investment in technology resources, continuous professional development for teachers, and flexible curriculum design. By implementing these recommendations, educational institutions can enhance their management strategies and ultimately improve English language learning outcomes for students